Droplet impact dynamics on a spherical particle - Mitra, S.; Sathe, M.; Doroodchi, E.; Utikar, Ranjeet; Shah, Milinkumar; Pareek, Vishnu; Joshi, J.; Evans, G. (Pergamon, 2013)
In this work, subcooled droplet impact on a highly thermally conductive spherical surface was investigated both theoretically and experimentally. Specifically, the effect of Weber number on spreading of droplets of three different liquids namely water, isopropyl alcohol and acetone was studied. The droplet shape evolution and surface wetting upon droplet impact at surface temperatures ranging between 20 °C and 250 °C were investigated using a high speed camera. Maximum droplet spread was measured and compared with available correlations. Generally wetting contact was observed at surface temperatures below or close to saturation temperature whilst a non-wetting contact was exhibited at surface temperatures significantly greater than the saturation temperature. The drop in surface temperature was found to be significantly lower in this non-wetting contact regime which led to significant reduction in heat transfer coefficient. Despite a very small temperature drop in the film boiling regime indicating small fraction of vaporization, Schlieren imaging of acetone droplets showed qualitative vapour field around the rebounding droplets. The droplet spreading patterns in cold condition and film boiling regime were simulated using the 3D CFD models which were found to be in good agreement with the experimental observations.